Potential Stichopus hermanii as a gingivitis inhibitor: Potensi Stichopus hermanii sebagai penghambat gingivitis - Amin, Asmawati; Aryadifa, Muhammad Arif; Rajab, Nur Indasari; Thalib, Alqarama Mahardhika; Thalib, Bahruddin; Zaizafun, Ainiyyah Fildza; Reni, Delvi Sintia (Makassar Dental Journal, 2024)
Gingivitis is a response to the buildup of bacterial plaque, characterized by symptoms such as bleeding, swelling, redness, and exudate. One of the marine biotas widely found in Indonesia is the golden sea cucumber (Stichopus hermanii), which contains va-rious bioactive components such as proteins, hyaluronic acid, chondroitin sulfate, EPA, DHA, and flavonoids. This systematic re-view aims to reveal the potential of Stichopus hermanii as a gingivitis inhibitor. The method used follows a systematic review ap-proach, adhering to the guidelines of the preferred reporting items for systematic reviews and meta-analyses (PRISMA). A total of 8 studies met the eligibility criteria to be included in this systematic review. It is concluded that the use of Stichopus hermanii has the potential to effectively reduce gingivitis.